Biofenomenologia da melancolia: uma reflexão sobre o estado da arte no tratamento da depressão e sua aplicação no sujeito subjetivo - Oliveira, Lucas Cleto de (Universidade Federal de São Carlos, 2023)
This course completion project presents a reflective qualitative review of the state of the art in depression treatment and its application to the subjective self. The review delves into the pathophysiology of depression, pharmacological strategies to expedite antidepressant response, and enhance antidepressant efficacy, including medication switching, combination of antidepressants, and co-administration of augmenting agents. It also discusses ketamine, an agent that produces an immediate and effective response in treating suicidal behavior, and the involvement of the nociceptive system in the pathophysiology of depression. The review introduces a paradigm describing the possibility of simultaneous action in three therapeutic response time frames in depression treatment: immediate, rapid, and slow. It discusses pharmacological agents with their respective properties. Furthermore, it emphasizes the importance of maximizing pharmacological therapeutic effects and remission rates, extending beyond cognitive, behavioral, or discursive strategies. The review analyzes the real impact of such optimizations on the author throughout their personal and academic experience. This review concludes that ketamine, an agent providing an immediate and effective response in treating suicidal behavior, could be a crucial factor in reducing the impact of depression on society, altering outcomes such as suicide and loss of functionality.
Biophenomenology of melancholy: a reflection on the state of the art in depression treatment and its application to the subjective self
Keywords: Depressão; Fisiopatologia; Antidepressivos; Farmacologia; Cetamina; CIENCIAS DA SAUDE::MEDICINA::PSIQUIATRIA